Formulation and Antioxidant Activity of Syzygium polyanthum (Salam) Ethanolic Extract with Het-Cam Irritation Assessment - Lina Widiyastuti; Siti Fatmawati Fatimah; Athiyyah Najelita Harahap; Leoni Nanda Wulandari; Hajjatuna Hasna Salsabil; Syifa Aulia Nugraheni; Aulia Salsabila Merdeksari (Universitas Muhammadiyah Yogyakarta, 2026)
Ethanol extract of salam leaves (Syzygium polyanthum) contains flavonoids, tannins, essential oils, citric acid, and eugenol, which are efficacious as antioxidants, anti-cholesterol, antimicrobials, and antidiabetics. Extracts need to be formulated in gel dosage forms to obtain uniform doses, enhance the effectiveness of pharmacological effects, ensure hygiene, and facilitate ease of use. The study aims to develop a gel formula using the physical characteristics ANOVA method with ethanol extract from salam leaves at a 95% confidence level. The results revealed that the salam leaves ethanol extract gel had moderate to strong antioxidant activity. The results of the irritation test indicate that the characteristics have met the requirements for efficacious antioxidant dosage forms that do not cause irritation. The stages of the research method began with the development of a gel dosage form using Design Expert software. The gel formed exhibited physical characteristics, including organoleptic properties, viscosity, homogeneity, pH, adhesion, and spreadability. The gel effectiveness test included an antioxidant test using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method and an in vitro irritation test using the Hen's Egg Test Chorioallantoic Membrane (HET-CAM) method, which assessed the presence of lysis, bleeding, or coagulation in the test media.